Effects of Rosemary and Green Tea Antioxidants on Ground Beef Patties in Traditional and Modified Atmosphere Packaging - Deborah L. VanOverbeke; Gretchen Mafi; Laura Yoder; Ranjith Ramanathan (Meat and Muscle Biology, 2021)
The objective of this study was to analyze the effects of rosemary (RSM) and green tea (GT) added to groundbeef to extend shelf life. Four antioxidant treatments were used: control, 2,500 ppm RSM, 300 ppm GT, and 2,500 ppm RSM + 300 ppm GT (RSM + GT). Patties from each treatment (n = 42) were randomly packaged into one of 3 types: polyvinyl chloride (PVC) overwrap, modified atmospheric packaging (MAP), or master packages (MP). Packages of MAP and MP were flushed with 0.4% CO, 69.6% nitrogen (N2), and 30% carbon dioxide (CO2). Patties in PVC and MAP were placed directly into display cases for 7 d, and MP patties were placed in dark storage for 7 d and then in display cases for another 7 d. Instrumental and subjective color, lipid oxidation, and sensory panel scores were measured. In MAP, patties with GT had increased (P < 0.05) a* and chroma values by day 6 of retail display. In MP at 3 d of retail display, GT patties exhibited increased (P < 0.05) L* values (lighter), display color (deeper red), and surface discoloration (greater discoloration) scores compared with RSM + GT patties. However, GT and RSM patties were not different (P > 0.05) for these parameters. Trained sensory panelists did not detect a difference between control and GT patties for the green-hay attribute; however, RSM patties had highly detectable (P < 0.05) green-hay flavor. Panelists were unable to detect any differences (P > 0.05) for rancid or fatty flavors regardless of treatment. Patties in MAP were more color stable than those in PVC after 6 d of retail display. In conclusion, patties in MP with GT showed positive instrumental and objective color measurements, as well as lipid oxidation values after 3 d of display, combined with undetectable flavor, warranting further research.